Coping with food price hikes: Strategies of the poor in Kandy, Sri Lanka - Sarath S. Kodithuwakku; Jeevika Weerahewa (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2011)
High food prices have consistently forced families to adopt a myriad of coping strategies to meet their food needs. A comprehensive understanding of the nature and diversity of such strategies, the relative effectiveness of different strategies, and the factors that determine the choice of various strategies by different vulnerable groups is of prime importance in designing and implementing appropriate policies and programs on vulnerable groups. The objectives of this study are to assess: (i) the resource profile of the vulnerable households in Kandy district in Sri Lanka, (ii) food consumption pattern of the households, (iii) the coping strategies adopted by the households during the times of food price hikes, (iv) the usefulness and effectiveness of coping strategies adopted by the household, and (v) the factors that influence the decisions made by households to change their food consumption patterns in crisis situations. A primary survey was conducted with randomly selected samples of 160, 148 and 147 poor households in Gangawata-Koralaya, Harispattuwa and Doluwa which represent to urban, rural and estate sectors in Kandy district respectively using a structured questionnaire. Data was analyzed using descriptive statistics and multi-nomial logit analysis where appropriate. The results show that a variety of strategies have been used by the poor households to cope up food price hikes. Cutting down of consumption of non-food items, borrowings from the informal markets and increased dependence on friends and families are the commonly used strategies that were perceived to be useful by the households. Curtailing of food consumption has been observed, in varying degrees in different sectors and for different food items. Reductions in frequency of consumption and portion size were noted particularly in urban and estate sectors for imported food items and substitution to local products, such as jack fruit, bread fruit and yams have been noted. These findings imply that the development practitioners should pay a closer attention to the sociocultural contexts when dealing with crises situations. The need for well articulated trade policies on imported food items, in particular wheat, sprat, soya, dhal, edible oil and milk, on which the households spends a larger share of expenditure, is highlighted.
Keywords: 330; Coping Strategies; Food Price Hikes; Sri Lanka